LEVERAGING TECHNOLOGY TO ENHANCE STUDENTS' PRACTICAL COMPETENCE IN ORGANIZING CLUBS - Abdullayeva Feruza Samatovna (American Journals, 2025)
This scientific article investigates the potential of technology in improving students' practical competence in organizing clubs. Clubs play a crucial role in fostering social skills, leadership abilities, and teamwork among students. By integrating technology into club management and organization processes, students can develop a wide range of practical skills, including communication, event planning, budgeting, and marketing. This paper reviews existing literature on the benefits of technology in club organization and provides insights into how educators and students can harness technology to enhance their club-related competencies.
Keywords: Technology integration, practical competence, student clubs, club organization, digital tools, leadership skills.